Recent advances in otitis media (B. C. Decker, 1996)
The book continues to advance our understanding of the epidemiology, etiology, pathogenesis, diagnosis and management of otitis media through both basic and clinical research. Otitis is pervasive and cortly, and often has lifelong consequences. Primarily a disease of children, it also affects adults and can be acute, subacute, or chronic. Otitis media has the distinction of being the commonest indication for antibiotic and eventually eliminated. The book elucidates risk factors, identifies pathogens, characterizes the bacterial-cell genomes. Most importantly, the devoplment of vaccines against the two major pathogens in otitis media, the pneumococcus and the nontypeable Haemophilus influenzae, is a certainty that will soon be realized